Defining Terrorism: how Ambiguous Definitions and Vague Classifications Open Doors for Power Acquisition - Anastassiya Mahon (Journal Of Global Strategic Studies, 2022)
In this article, I want to reflect on the difficulty of categorising the threat of terrorism within existing security frameworks and our theorising of threat assessment. As more types of terrorism get academic and political attention, various state and non-state actors use terrorist tactics or borrow some elements of terrorism to achieve their agenda. This article discusses the difficulties surrounding terrorist threat classification and how it perplexes our understanding of terrorism and counterterrorism. What have we learned over more than twenty years of researching terrorism? Terrorism is often conceptualised as both a traditional and non-traditional threat, complicating the execution of counterterrorism strategies. This ambiguity creates the need for a "special treatment" of the terrorist threat in politics proportionate to its importance, and it bears the danger of fostering opportunities for power abuse. This article reflects on different ways of categorising the threat of terrorism, showing that terrorism is multifaced, and there is no one-size-fits-all approach to defining and fighting terrorism. However, I also argue that there is a danger of assigning terrorism an extralegal status and exclusive priority, resulting in power abuse and restrictions of people's rights and freedoms.